Advancing Intercultural Competence in Higher Education: Strategies for Engaging Generation Z - Yamada, Aki (Education sciences, 2025)
This study examines how Japanese Generation Z, “digital natives” currently in higher education, engage in cross-cultural learning and develop global skills. In the modern digital era, encountering and studying international topics, cultures, and languages is no longer limited to the traditional physical movement of people to acquire new experiences. We seek to investigate a modernized educational model for intercultural exchange, learning, and internationalization that emphasizes the technological information, platforms, and tools that the digital native generation uses daily. We use survey data from 123 Japanese higher-education students to investigate this subject and help reveal how they can operate and learn global skills in an increasingly digital landscape. Our findings indicate a strong desire to gain intercultural competence through digital sources, remote communications, and interactions with inbound international students. Digital information provides a significant opportunity for students to gain foundational international knowledge and competencies without the level of investment and limited accessibility of traditional study-abroad programs. We consider the pros and cons of integrating digital information into future academic endeavors.